Nonvolatile Electric Control of Exchange Bias by a Redox Transformation of the Ferromagnetic Layer - Zehner, Jonas; Huhnstock, Rico; Oswald, Steffen; Wolff, Ulrike; Soldatov, Ivan; Ehresmann, Arno; Nielsch, Kornelius; Holzinger, Dennis; Leistner, Karin (Advanced Electronic Materials, 2019)
Electric manipulation of exchange bias (EB) systems is highly attractive for the development of modern spintronic and magnetophoretic devices. To date, electric control of the EB has mainly been based on multiferroic or resistive switching behavior in specific antiferromagnets, which limits the material choice and accessible EB states. In addition, the effects are mostly volatile, requiring constant voltage application. The continuous and nonvolatile tuning of the EB via electrochemical manipulation of the ferromagnetic layer is presented. In FeOx/Fe/IrMn systems, large changes in the EB field of fully shifted magnetization curves are achieved at low voltage (<1 V) and room temperature. A ferromagnetic-layer thickness change resulting from the electrochemical reduction of iron oxide to iron is proposed as the underlying mechanism and is consistent with a simple model for the EB and surface analysis. Nonvolatility is achieved as the reduction proceeds at the buried FeOx/Fe interface, leaving the remaining oxide as a protective layer. A lateral voltage-controlled patterning of the EB fields and magnetic domain state is demonstrated. This versatile redox-based electric control of the EB paves a new route for the design of EB systems in general and for the development of future electrically controlled EB devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: exchange bias; magnetic domains; magnetoionics; redox reaction; voltage control of magnetism